Bibliometrijska analiza revije Jezik in slovstvo - Jambrovič, Terezija (Jezik in slovstvo, 1999)
The present bibliometric analysis of the Slavonic studies journal Jezik in slovstvo is the first of its kind in Slovenia. Its results should be interpreted only in co-operation with the experts from the field being analysed. It may also serve as a pilot study for possible future systematic analysis of Slovene scientific journals and magazines, which are for obvious reasons not indexed in international citation indexes. The model of analysis uses the metodology of these indexes. The objective of such an analysis would be obtaining information on the impact and visibility of published research data also in those fields that have so far not been scrutinised by bibliometric instruments.
Keywords: bibliotekarstvo; library science; klasifikacija; bibliometrija; revije; Jezik in slovstvo